Official work in Ukraine: characteristics of legal status and recurring problems - Pokalchuk, Mykhailo; Sokh, Kateryna; Yalova, Oksana; Zubkova, Liubov; Borovska, Iryna (Cuestiones Políticas, 2020)
The purpose of the article is to analyze the concept of "contract work" in Ukrainian legislation, determine its characteristics, as well as identify the scope of rights that arise with its creation. The methodological basis of the research is a series of general and special scientific methods of cognition. In the research process, formal and logical methods, systems and structural, comparative and legal, logical and legal and other scientific research methods were used. The rules of Ukrainian legislation, which regulate the subject under consideration, were investigated; they were compared with the relevant laws of some states of the world. Judicial practice, which deals with some problems related to the distribution of contract work rights between an employer and an employee, was also examined. Practical implication. The concept of "paid work" in the Ukrainian legislation was analyzed, its characteristics were identified, which are at the same time the conditions for recognizing work as paid work. By way of conclusion, it is convenient to distinguish the non-patrimonial and property rights of an employer and employee to work under contract, which in turn implies the problem of determining the amount of royalties.